Unveiling Maja Labo Dahu: a Local Wisdom in Implementing Character Values - Irwan, Irwan; Haris, Abdul; Khozin, Khozin; Hendra, Hendra; Anwar, Saiful (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This study focuses on the importance of imparting character values by incorporating local cultural wisdom, specifically Maja Labo Dahu, within the curriculum of Al-Maliki Islamic Junior High School. This research aims to uncover and evaluate the application of the moral principles associated with religious beliefs among students, using Maja Labo Dahu as a reference point. This particular study falls under the category of qualitative research. Data collection methods include conducting interviews, making observations, and gathering documentation. Data analysis techniques involve using reduction, presentation, and conclusion. The findings indicated that: Firstly, integrating the significance of Maja Labo Dahu into all pertinent materials; Secondly, enhancing educational methods that foster critical thinking, integrity, collaboration, appreciation for diversity, respect for differing viewpoints, reliability, tolerance, democracy, bravery in expressing ideas, and accountability. Maja Labo Dahu's character values are implemented when converting information for students and arranging programs, education, and specialized training centered around Maja Labo Dahu's character values. After that, assessments conducting observations are conducted concurrently to evaluate the progress of the learning process that has been executed with techniques that can promote Maja Labo Dahu's character. Utilizing Maja Labo Dahu as a form of indigenous cultural heritage can be a valuable asset to the communal existence. When viewed as a reflection of one's personality and beliefs, this particular value is highly suitable for nurturing a religious character.